Sodium zirconium phosphate‐based glass‐ceramics as potential wasteforms for the immobilization of nuclear wastes. Issue 2 (25th October 2021) - Scales, Nicholas; Dayal, Pranesh; Aughterson, Robert D.; Zhang, Yingjie; Gregg, Daniel J.
Abstract: A comprehensive study on the development of sodium zirconium phosphate (NZP)‐based glass‐ceramic composites as potential wasteforms for the immobilization of nuclear wastes is reported. Two complementary waste treatment routes, the ex situ and in situ crystallisation of NZP with a sodium aluminoborosilicate glass, were investigated with various processing conditions including sintering temperature, cooling rate and NZP to glass ratios. While the ex situ route with mixing of pre‐made NZP and glass is a robust and reliable means of producing the glass‐ceramic composites, the in situ crystallisation of NZP from an amorphous NZP precursor is a more realistic processing route. The formation of ZrO2 as a minor phase was observed especially for high NZP to glass ratios due to the solubility difference between Zr and P oxides in glass. The addition of extra phosphate can overcome this and yield glass‐ceramic composites with appropriate NZP stoichiometry. Overall, the NZP glass‐ceramic system is versatile offering multiple processing options for nuclear waste management. Abstract : A comprehensive investigation on the development of sodium zirconium phosphate (NZP)‐based glass‐ceramic composites as candidate wasteforms for the immobilization of nuclear wastes is reported.